Combination Chemotherapy with Firocoxib Induces Reduction of Regulatory T Cells in Dogs with Multicentric B Cell Lymphoma - Anai, Leticia Abrahao [UNESP]; Munhoz, Thiago Demarchi; Souza Semolin, Livia Maria [UNESP]; Fonseca, Denise Morais da [UNESP]; Jark, Paulo Cesar; Ruiz Sueiro, Felipe Augusto; Calazans, Sabryna Gouveia; Costa, Mirela Tinucci [UNESP]; Santana, Aureo Evangelista [UNESP] (Univ Agriculture, Fac Veterinary Science, 2019)
The aim of this study was to quantify T cells (CD4+, CD8+ and Treg), in dogs with multicentric lymphoma treated with a conventional CHOP protocol or with one in which firocoxib was used instead of prednisone. Twenty-one dogs with lymphoma were divided into two treatment groups (G1=10 and G2=11): those that received the conventional CHOP protocol for 19 weeks (CHOP group) and those that received CHOP protocol with firocoxib instead of prednisone (CHOF group). Twelve clinically healthy dogs were used as control. The percentage of Treg cells were three times greater in animals with lymphoma than in the control group (P<0.05). During treatment, the reduction in Treg cells was slower in animals treated with firocoxib than in those that received prednisone. No significant difference (P>0.05) was observed in survival time between the two treatment protocols. It can be concluded that the use of firocoxib instead of prednisone in CHOP protocol can induce Treg cell remission in dogs with multicentric lymphoma without interfering with the survival time of these animals. (C) 2019 PVJ. All rights reserved
Keywords: Canine lymphoma; CHOP; Foxp3; Treg